2018
DOI: 10.3389/fnhum.2018.00198
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-Related Consciousness Detection in Patients With Disorders of Consciousness Through an EEG-Based BCI System

Abstract: For patients with disorders of consciousness (DOC), such as vegetative state (VS) and minimally conscious state (MCS), detecting and assessing the residual cognitive functions of the brain remain challenging. Emotion-related cognitive functions are difficult to detect in patients with DOC using motor response-based clinical assessment scales such as the Coma Recovery Scale-Revised (CRS-R) because DOC patients have motor impairments and are unable to provide sufficient motor responses for emotion-related commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 54 publications
2
41
0
1
Order By: Relevance
“…In terms of the arousal space, higher frequency (beta, gamma) components from electrodes positioned on all positions have a higher correlation. Our results are partially consistent with the findings of previous work [35]. Pan et al found that the neural patterns had significantly higher responses in low frequencies at prefrontal sites and significantly higher theta and alpha responses at parietal sites for sad emotions and valence is a measure of both positive and negative emotion [35].…”
Section: Discussionsupporting
confidence: 93%
“…In terms of the arousal space, higher frequency (beta, gamma) components from electrodes positioned on all positions have a higher correlation. Our results are partially consistent with the findings of previous work [35]. Pan et al found that the neural patterns had significantly higher responses in low frequencies at prefrontal sites and significantly higher theta and alpha responses at parietal sites for sad emotions and valence is a measure of both positive and negative emotion [35].…”
Section: Discussionsupporting
confidence: 93%
“…The correlation from the frontal head is slightly higher than that in posterior of the head. The findings are in line with the previous work [66].…”
Section: Preliminary Correlation Analysissupporting
confidence: 93%
“…The left superior temporal gyrus (STG, BA38) is dedicated to language processing, while the right side is considered the center of spatial awareness 55 . It is also important for social emotion processing 56 and facial emotion 57 . Interestingly, adolescents with a suicide attempt history show reduced grey-matter volume in the right BA38 58 60 .…”
Section: Discussionmentioning
confidence: 99%